Prevenção de coerção em sistemas de votação eletrônica baseados em blockchain: uma revisão sistemática - Araujo, Carlos Jefferson Soares (2024)
Blockchain is a technology that is being widely used in various contexts to solve numerous problems. In this sense, Blockchain is present in electronic voting systems. Any electoral process has several properties that must be satisfied. From the accreditation and identification stage, through the voting phase, to the post-election period, many threats to the integrity of the electoral process can occur. Consequently, computerized electoral systems can leverage the properties of the Blockchain. One of the threats to a specific electoral system arises through coercion, which occurs when an individual induces or pressures someone to do something through force, intimidation, or threats. The main purpose of this study is to identify methods used to inhibit coercion in electronic voting systems that utilize Blockchain. To achieve this goal, a systematic literature review was conducted according to the principles of the PRISMA protocol. The literature was accessed and selected from the following databases: SCOPUS, IEEE Xplore, and Springer Link. 25 articles were chosen for analysis. The analyses of this literature indicate that the characteristics of Blockchain align as solutions to many challenges of electoral systems, especially regarding the robustness and reliability of the system. The future of elections will have Blockchain as one of the protagonists, and the systems will meet the key demands of an electronic voting system.